Child Custody After Divorce Perspective of Islamic Law (JURNAL HUKUM SEHASEN, 2020)
Divorce due to the influence of social media is not only caused by the fact that their partner is having an affair, but the influence of social media in general also cannot be denied that someone will experience social media addiction. There are many people who are not able to manage their time so that the time that should be spent with their family must be lost because the hours are too cool to chat and cannot be separated from cyberspace / chat / social media.